ANALISA WAKTU TEMPUH KENDARAAN RODA DUA PADA RUAS JALAN ARTERI PRIMER KOTA SAMARINDA - Wahyudi, Slamet (KURVA S JURNAL MAHASISWA, 2014)
Travel Time is the average time used the vehicle to travel the road segment with certain length, including delays, downtime, the average travel time of vehicles, obtained from comparing the length of the road segment L (km). Speed and travel time varies with time, space and intermodal. Variations over time due to changes in traffic flows, the mixing of the type of vehicle and driver groups, lighting, weather and traffic events.As a primary arterial road in the city of Samarinda, Jalan Fortunately Soerapatti - Yos Sudarso used to serve regional traffic flow and continuously with the characteristics of the movement of vehicles which have a maximum speed of 60 km / h. Due to the influence of the development of the city of Samarinda, the development activities of the Road Fortunately Soerapatti - Yos Sudarso also very rapidly, as evidenced by the more intense the activity along the primary arterial road. This causes an increase in the intensity of the movement of both people and goods at Road Fortunately Soerapatti - Yos Sudarso very high, and results in an increase in volume of vehicles on the road segment.The method used for data retrieval Travel Time using the tool of GPS (global positioning system) to obtain the vehicle speed per second. While the modeling method of travel time of two-wheeled vehicles were analyzed using multiple linear regression (SPSS 20.0).There are three variables that significantly affect the travel time of the vehicle. These three variables showed signs of rationality test the suitability of the travel time. Wherein the increasing value of the variable is positive lead vehicle travel time will be growing, while the increasing value of the variable is negative causing the vehicle travel time will be reduced. Overall, the value of the indicator is a good level of fitness model, as indicated by the R2 value of 0.999 models.